Making information and communications technologies (ICTs) work for health: protocol for a mixed-methods study exploring processes for institutionalising geo-referenced health information systems to strengthen maternal neonatal and child health (MNCH) service planning, referral and oversight in urban Bangladesh - Shaikh Mehdi Hasan; Alayne Mary Adams; Rushdia Ahmed; Rubana Islam; Dipika Shankar Bhattacharyya; Sohana Shafique (BMJ Open)
Introduction Disparities in health outcomes and access to maternal neonatal and child health (MNCH) are apparent among urban poor compared with national, rural or urban averages. A fundamental first step in addressing inequities in MNCH services is knowing what services exist in urban areas, where these are located, who provides them and who uses them. This study aims to institutionalise the Urban Health Atlas (UHA)—a novel information and communications technology (ICT) tool—to strengthen health service delivery and oversight and generate critical evidence to inform health policy and planning in urban Bangladesh.Methods and analysis This mixed-method implementation research will be conducted in four purposively selected urban sites representing larger and smaller cities. Research activities will include an assessment of information needs and task review analysis of information users, stakeholder mapping and cost estimation. To document stakeholder perceptions and experiences, key informant interviews and in-depth interviews will be conducted along with desk reviews to understand MNCH planning and referral decisions. The UHA will be refined to increase responsiveness to user needs and capacities, and hands-on training will be provided to health managers. Cost estimation will be conducted to assess the financial implications of UHA uptake and scale-up. Systematic documentation of the implementation process will be undertaken. Policy decision-making and ICT health policy process flowcharts will be prepared using desk reviews and qualitative interviews. Thematic analysis of qualitative data will involve both emergent and a priori coding guided by WHO PATH toolkit and Policy Engagement Framework. Stakeholder analysis will apply standard techniques and measurement scales. Descriptive analysis of quantitative data and cost estimation analysis will also be performed.Ethics and dissemination The study has been approved by the Institutional Review Board of icddr,b (# PR-16057). Study findings will be disseminated through national and international workshops, conferences, policy briefs and peer-reviewed publications.